Selenium and functional constipation in children - Marlina Tanjung; Supriatmo Supriatmo; Melda Deliana; Ade Rachmat Yudiyanto; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2016)
Background Constipation is a common problem in children, with approximately 90 to 95% of constipation cases having functional constipation. Oxidative stress may be a causative factor in gastrointestinal diseases, alleved by intervention with antioxidants. Selenium is an essential trace element and acts as a cofactor of gluthathione peroxidase, which protects membranes from oxidative damage.Objective To determine the effect of selenium on functional constipation in children.Methods We conducted a single-blind, randomized clinical trial from November to December 2012 at the Al-Kautsar Al-Akbar Islamic Boarding School in Medan, North Sumatra. Subjects were children aged 12 to 17 years with functional constipation, diagnosed according to the ROME III criteria. Patients were randomly allocated into either the selenium group (n=57) or the placebo group (n=57). Subjects were clinically evaluated for frequency of defecation, stool consistency, severity of abdominal pain, and side effects during the 2 weeks of treatment (days 7 and 14) and 1 week after treatment had stopped (day 21).Results A total of 114 subjects were eligible to participate. The average frequency of defecation observed on day 14 was 1.5 (SD 0.75) days per defecation (P=0.0001) in the selenium group and 2.4 (0.84) days per defecation in the placebo group, a statistically significant difference (P=0.0001). There was no significant difference in frequency of defecation on the 7th day of treatment. But after day 7, there were significant differences between the groups at days 14 and 21. Normal stool consistency was found in 45 subjects (78.9%) on day 7 and in 57 subjects (100%) on day 14 of treatment in the selenium group, significantly more than those in the placebo group (P<0.05). In placebo group, normal stool consistency was found in 27 subject (47.4%) with (P=0.001) on day 7 and in 38 subject (66.7%) on day 14 of treatment (P=0.0001). On day 14, the selenium group had significantly more subjects without pain than the placebo group [47 subjects (82.5%) vs. 10 subjects (17.5%), respectively (P=0.0001)]. Severity of abdominal pain after 14th day of treatment is without pain 47 subject (82.5%) and mild pain 10 subject (17.5%) (P=0.0001). We found no side effects of selenium treatment in our subjects.Conclusion Selenium is effective in improving clinically functional constipation, in terms of increased frequency of defecation, normalization of stool consistency, and less severe abdominal pain.